2013
DOI: 10.1186/1754-6834-6-43
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the lignin distribution in pretreated sugarcane bagasse by confocal and fluorescence lifetime imaging microscopy

Abstract: BackgroundDelignification pretreatments of biomass and methods to assess their efficacy are crucial for biomass-to-biofuels research and technology. Here, we applied confocal and fluorescence lifetime imaging microscopy (FLIM) using one- and two-photon excitation to map the lignin distribution within bagasse fibers pretreated with acid and alkali. The evaluated spectra and decay times are correlated with previously calculated lignin fractions. We have also investigated the influence of the pretreatment on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 30 publications
5
45
0
3
Order By: Relevance
“…The hydrostatic pressures within cell wall layers then force a fraction of these lignin aggregates to the outer face of biomass which in turn contact with the pretreatment bulk solvent and deposit back onto cell wall surfaces [63,108]. Using confocal and fluorescence lifetime imaging microscopy, Coletta et al [112] observed that DAP resulted in a disorder in the arrangement of lignin and its accumulation in the external border of cell walls. Donohoe et al [106] have proposed that lignin migrating/ relocating to a more localized and concentrated distribution in outer cell walls during acidic pretreatments can dramatically open up the structure of cell wall matrix and improve the accessibility of majority of cellulose microfibrils, which enhances the pretreated biomass digestibility.…”
Section: Lignin Relocation and Redistributionmentioning
confidence: 97%
“…The hydrostatic pressures within cell wall layers then force a fraction of these lignin aggregates to the outer face of biomass which in turn contact with the pretreatment bulk solvent and deposit back onto cell wall surfaces [63,108]. Using confocal and fluorescence lifetime imaging microscopy, Coletta et al [112] observed that DAP resulted in a disorder in the arrangement of lignin and its accumulation in the external border of cell walls. Donohoe et al [106] have proposed that lignin migrating/ relocating to a more localized and concentrated distribution in outer cell walls during acidic pretreatments can dramatically open up the structure of cell wall matrix and improve the accessibility of majority of cellulose microfibrils, which enhances the pretreated biomass digestibility.…”
Section: Lignin Relocation and Redistributionmentioning
confidence: 97%
“…The above assignments are corroborated by the fact that the cellulose samples presented crystallinities of about 70% [41], a percentage that can be obtained directly from the ratio of the signal observed for Pake and Gaussian spectral components for MC >10%. 2 H NMR should be used for the correct study of water molecules dynamics under low humidity levels.…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…Coletta etal. [24] used confocal and fluorescence lifetime imaging microscopy to map the lignin distribution in pretreated sugarcane bagasse after acid and alkali pretreatments and a study of different types of wood cell walls to localize cellulose and lignin was performed by Bond et al [25].…”
Section: Introductionmentioning
confidence: 99%